Dayah MUDI Samalanga in Aceh: Teungku Authority, Sociocultural Religion, and the Popularity of an Islamic Education Center - Husna, Fathayatul; Sariyanti, Lilis; Fitri, Ainal; Nova, Mirza Adia (Universitas Islam Negeri Ar-Raniry Banda Aceh, Aceh, Indonesia., 2025)
This study examines Dayah MUDI Samalanga as an Islamic education center within the sociocultural context of Aceh, focusing on teungku authority and the institution’s contemporary popularity. While modernization and digital communication are often assumed to weaken traditional religious authority, this article argues that teungku authority persists and is rearticulated through institutional visibility, community engagement, and media practices. Employing a qualitative approach using virtual ethnography (netnography), the study analyzes publicly accessible institutional digital content—including the official website, social media platforms, and video-based channels—alongside relevant literature to trace how authority and institutional identity are narrated in online public spaces. The findings show that teungku authority remains a key source of legitimacy for Dayah MUDI, constructed through scholarly credibility, symbolic positioning, and continuity of religious traditions. The popularity of Dayah MUDI is shaped by the interaction of leadership authority, institutional branding, educational modernization (including the expansion of higher education initiatives), and sustained media visibility through social media and institutional broadcasting channels. Digital media therefore function not merely as communication tools but as arenas where religious authority and institutional identity are publicly reproduced and extended beyond local communities. This study contributes to discussions on religious authority, Islamic education, and digital mediation by demonstrating that dayah institutions actively negotiate continuity and change in contemporary socioreligious environments. Abstrak Penelitian ini mengkaji Dayah MUDI Samalanga sebagai pusat pendidikan Islam dalam konteks sosiokultural Aceh, dengan menyoroti otoritas teungku serta popularitas institusi tersebut pada masa kini. Di tengah asumsi bahwa modernisasi dan komunikasi digital cenderung melemahkan otoritas keagamaan tradisional, artikel ini berargumen bahwa otoritas teungku tetap bertahan dan mengalami reartikulasi melalui visibilitas institusional, keterlibatan komunitas, serta praktik-praktik media. Dengan menggunakan pendekatan kualitatif melalui etnografi virtual (netnografi), penelitian ini menganalisis konten digital institusional yang dapat diakses publik, meliputi situs web resmi, platform media sosial, dan kanal berbasis video, serta literatur relevan untuk menelusuri bagaimana otoritas dan identitas institusi dinarasikan dalam ruang publik daring. Temuan menunjukkan bahwa otoritas teungku tetap menjadi sumber legitimasi utama bagi Dayah MUDI, yang dibangun melalui kredibilitas keilmuan, peneguhan simbolik, dan kesinambungan tradisi keagamaan. Popularitas Dayah MUDI dibentuk oleh interaksi antara otoritas kepemimpinan, praktik branding institusional, modernisasi pendidikan (termasuk ekspansi inisiatif pendidikan tinggi), serta visibilitas media yang berkelanjutan melalui media sosial dan kanal penyiaran institusional. Media digital, karenanya, berfungsi bukan semata sebagai alat komunikasi, tetapi juga sebagai arena reproduksi otoritas keagamaan dan identitas institusi, sekaligus memperluas jangkauan pengaruhnya melampaui komunitas lokal. Studi ini berkontribusi pada diskusi tentang otoritas keagamaan, pendidikan Islam, dan mediasi digital dengan menunjukkan bahwa dayah secara aktif menegosiasikan kesinambungan dan perubahan dalam lingkungan sosioreligius kontemporer.